Development of an RFID-Based Application for Medical Equipment Inventory Record Maintenance - Harikaran, Sivajothi; Vajravelu, Ashok (Evolution in Electrical and Electronic Engineering, 2025)
The proposed project focuses on developing a device and a system that utilize RFID technology that will change the way health inventory is managed. Built within the Android Studio and implemented using Java programming language and connected to a phpMyAdmin database through PHP, this application helps maintain records of inventories. Through issuing unique RFID tags to the equipment it is easier to retrieve data since after scanning the RFID tags all the details of the specific equipment is retrieved without necessarily going through other details of other pieces of equipment thus saves time. It guarantees the proper store of functional medical equipment, increases the accuracy level of inventory, and leads to the improvement of the overall patient care, which proves the effectiveness of RFID imagery’s role in the digital disruptiveness of healthcare.